DIAGNOSTICS, DIFFERENTIAL DIAGNOSTICS AND THE TREATMENT OF PANDAS SYNDROME. CASE DESCRIPTION - Mukhtorjonova Khusnigul Nodirbekovna; Tukhtabayeva Kamila Abrarovna (Scholar Express Journals, 2022)
This article gives a case of PANDAS syndrome in an 11-year-old boy. The course and clinic of the disease in the form of prolonged sneezing attacks made it difficult to diagnose this syndrome. Conducting biochemical blood tests, daily video electroencephalographic monitoring (EEG monitoring) and magnetic resonance imaging of the brain (MRI) allowed to determine the condition. The appointment of antibiotic therapy and intravenous administration of immunoglobulin led to remission of the disease. It is necessary to conduct further studies to determine the effectiveness of the above drugs for this syndrome.
Keywords: Tics; PANDAS Syndrome; EEG